2012
DOI: 10.3183/npprj-2012-27-01-p137-142
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of fibre orientation probability distribution in the jet-to-wire impingement

Abstract: Fibre orientation distribution is essential factor affecting the properties of produced paper. The fibre orientation distribution is mainly determined by the fluid dynamics in the wet-end and in the wire-section of the paper machine. In this work the fibre orientation probability distribution in the paper machine jet-to-wire impingement is studied using modelling. The model used in this work is based on diffusion-convection equation. In addition to the transport of the fibres due to the mean flow, the model in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…As mentioned in the introduction, the preferred fiber orientation is a complex function of jet, wire, and drainage speeds. Niskanen [17] showed that the orientation distribution of the fibers in the suspension can be approximated as an elliptic function of jet-wire speed difference and drainage speeds. In our simulations, we initially orient the suspended fibers with the same orientation distribution function.…”
Section: Fiber Deposition Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned in the introduction, the preferred fiber orientation is a complex function of jet, wire, and drainage speeds. Niskanen [17] showed that the orientation distribution of the fibers in the suspension can be approximated as an elliptic function of jet-wire speed difference and drainage speeds. In our simulations, we initially orient the suspended fibers with the same orientation distribution function.…”
Section: Fiber Deposition Modelmentioning
confidence: 99%
“…Due to the speed difference between the jet and wire, hydrodynamic shear acts on the fibers in the MD. As a result, the commercially formed sheets manifest a preferential fiber orientation in the MD [17]. The fabric is a permeable surface with an associated weave pattern, designed to facilitate water drainage while retaining fibers, fines, fillers, and additives.…”
Section: Introductionmentioning
confidence: 99%